Certain Geometric Properties of Normalized Wright Functions. (27th December 2016) - Raza, Mohsan; Din, Muhey U; Malik, Sarfraz Nawaz
Abstract : In this article, we find some geometric properties like starlikeness, convexity of order α, close-to-convexity of order 1 + α / 2, and close-to-convexity of normalized Wright functions with respect to the certain functions. The sufficient conditions for the normalized Wright functions belonging to the classes T γ α and L γ α are the part of our investigations. We also obtain the conditions on normalized Wright function to belong to the Hardy space H p .